Consistency verification in modeling of real-time systems - Yi Deng; Jiacun Wang; Zhou, MengChu (IEEE transactions on robotics and automation, 2004)
To real-time system designers, end-to-end time delay between external inputs and outputs is among the most important constraints. To ensure these system-wide constraints are satisfied, each of the constituent components is subject to a set of derived intermediate constraints. Since the system-wide constraints allow many possibilities for the intermediate constraints based on design tradeoffs, an important issue is how to guarantee the consistency between system-wide constraints and intermediate component constraints. In this paper, we present a systematic method for the verification of consistency between a system's global timing constraints and intermediate component constraints. The essence of this technique is to construct a timing model for each component, based on component constraints. This model treats a component as a black box. When replacing each component with its timing model, we obtain a complete time Petri net model for system architecture, which allows us to verify the consistency between global and component constraints. The key contribution is twofold. First, our technique of verification is efficient by supporting incremental analysis and suppressing internal state space of components. Second, much of the verification process presented in this paper can be automated. We illustrate the consistency verification process through a flexible manufacturing system example.